Pengembangan Bahan Ajar Cetak Pendidikan Agama Islam Berbasis Mind Mapping - Haeril Haeril; Muhammad Yaumi; Usman Usman; La Ode Ismail Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This paper discusses the validity, practicality, and effectiveness of a printed teaching material product developed based on Mind Mapping. This type of research is development research to produce certain products and test the effectiveness of these products. The location of this research was carried out at SMA Negeri 9 Marusu kab. Maros. The development of this teaching material refers to the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The data were analyzed to determine the level of validity, practicality, and effectiveness of the products that have been developed. The results showed that 1) The validity of the mind mapping-based Islamic Religious Education teaching materials at SMA Negeri 9 Marusu, Maros Regency. Based on the validation carried out by the validator, the validity results are obtained, namely, content validity, linguistic validity, presentation validity, and graphic validity; 2) The practicality of mind mapping-based Islamic Religious Education teaching materials at SMA Negeri 9 Marusu, Maros Regency. The practicality of the module data is in the very good category because the score obtained from the average student response values is 85% with a range of 81%-100%; and 3) The effectiveness of mind mapping-based Islamic Religious Education teaching materials to improve student learning outcomes at SMAN 9 Marusu, Maros Regency. Based on the results of the effectiveness test, the value of R = 6.81 was obtained. The data obtained means that R> 1, effectively 02 is more effective than 01. So the posttest is more effective.